Sá de Miranda by Camilo Castelo Branco - Franco, Marcia Arruda (2025)
Camilo’s essay on Sá de Miranda was written within the hommages that took place 300 years after the death of Camões. He meant to defend some thesis that question other readers of the pre-camonian poet, however he agrees with the eighteenth critical annalysis over Miranda’s new poetry.